Changes in High-Risk HPV Infection Prevalence and Associated Factors in Selected Rural Areas of China: A Multicenter Population-Based Study - Yu, Yan-Qin; Jiang, Ming-Yue; Dang, Le; Feng, Rui-Mei; Bangura, Mohamed S.; Chen, Wen; Qiao, You-Lin (Frontiers in Medicine, 2022)
Background The Chinese government has taken action to prevent cervical cancer by implementing the National Cervical Cancer Screening Programme in Rural Areas (NACCSPRA), which was launched in 2009. Numerous studies have demonstrated that long-term cervical cancer screening alters human papillomavirus (HPV) infection rates and cervical disease detection. Nearly 80 million women have been screened over 10 years, representing <30% of the target population; however, in some rural areas, such as Ordos City of Inner Mongolia Autonomous Region, Xiangyuan County of Shanxi Province, and Jinyun County, and Jingning County of Zhejiang Province, programs for prevention and treatment of cervical cancer have been implemented. Numerous studies have demonstrated that long-term cervical cancer screening alters rates of human papillomavirus (HPV) infection and cervical disease detection. In this study, we aimed to determine the infection rates of high-risk HPV (hrHPV) and the detection rate of cervical lesions; and changes in factors associated with cervical cancer, to provide scientific data to inform efforts to eliminate cervical cancer in rural areas. Methods This was a cross-sectional, population-based, and multi-center survey. Populations from three rural areas of China (Ordos City of Inner Mongolia Autonomous Region, Xiangyuan County of Shanxi Province, and Jinyun County and Jingning County of Zhejiang Province) were selected and 9,332 women aged 20–64 years old were invited to participate in cervical cancer screening by both cytology and HPV testing. The outcomes assessed were: infection rates with hrHPV, HPV16, 18, 16/18, and other 12 hrHPV types (HPV 31,33,35,39,45,51,52,56,58,59,66 and 68); detection rates of cytological and histological lesions; and factors associated with HPV infection. Results A total of 9,217 women aged 45.62 ± 8.02 years were included in this study. Infection rates with hrHPV, HPV 16, 18, 16/18, and other 12 hrHPV types were 16.3%, 3.0%, 1.5%, 4.3%, and 13.6%, respectively. There were significant differences among the age-specific HPV infection rates (P < 0.05). Infection rates with hrHPV, 16, 18, 16/18, and the other 12 hrHPV types showed a single peak infection mode, with a peak age of 56–65 years old. Age, marital status, number of live births, education level, reproductive disease history, and a history of alcohol consumption were risk factors for hrHPV infection. The detection rate of cytological abnormalities was 12.98% in the study and was higher in women older than 56 years old. The detection rates of cervical intraepithelial neoplasia CIN2+ and CIN3+ in the population were 1.45% and 0.77%, respectively. The highest incidence rates of CIN2+ and CIN3+ were 32.12% and 17.51%, respectively, in the 41–45 years old group. Conclusion Infection rates with hrHPV, HPV16, and cervical lesions among our screening population were lower than the mean level in rural areas of China. Infection rates with hrHPV, HPV16, 18, and 16/18 showed a single-peak infection pattern, with the peak age of infection being 56-65 years old. Risk factors for hrHPV infection were age, history of alcohol consumption, marital status, reproductive diseases, education level, and the number of live births. Based on these data, we recommend that cervical cancer screening be offered to women older than 30 years in rural areas, particularly those aged 41–45 years.